Artura Kozaka cierpliwość wobec prawa - Pichlak, Maciej (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The essay treats on a legal-theoretical project of ‘iuriscentrism’, proposed by Polish legal philosopher Artur Kozak. It begins with an exploration of theoretical and axiological foundations of this theory, which are, first and foremost, sociological institutionalism (as for a social ontology), philosophical transcendentalism (as for a theory of knowledge and action), and affirmative approach towards axiological foundations of the legal order. Subsequently, the article focuses on practical consequences of the above choices, which are a limitation of the judicial discretional power, and a unique way of legitimating the legal practice. According to iuriscentrism, the law is said to play a focal role in the contemporary, ethically pluralist and functionally differentiated societies; for those reasons a special approach to the legal order, the one termed as ‘a faith in law’ or ‘a patience to the law’, is necessarily required.